Influência do treinamento físico na remodelação cardíaca de ratos expostos cronicamento à fumaça de cigarro - Venturi, Diogo Grativol (2013)
Exposure to cigarette smoke in animals causes cardiac remodeling. Cardiac remodeling can be defined as a number of variations molecular, cellular, and interstitial cardiac which will manifest clinically as changes in size, mass, geometry and function of the heart in response to a given aggression. Chronic exposure to cigarette smoke causes increased blood pressure, ventricular hypertrophy, reduction of cardiac and endothelial dysfunction. Already physical training promotes lowering blood pressure, ventricular hypertrophy, increased and / or improved cardiac function and improves endothelial function. Cardiac remodeling promoted by exposure to cigarette smoke is characterized by cardiac hypertrophy accompanied by reduced function, a mechanism named as responsible is to pressure overload. Already remodeling promoted by aerobic PF is characterized by a kind of eccentric cardiac hypertrophy accompanied by an increase in cardiac function and reduce blood pressure. Thus we hypothesized that cardiac remodeling by exposure to cigarette smoke can be attenuated by physiological cardiac adaptations (physiological remodeling) promoted by physical training in swimming rats. Objective of this study is to analyze the influence of left intraventricular pressure changes in ventricular remodeling in rats from exposure to cigarette smoke and physical training with swimming. Therefore, we used 45 male Wistar rats, initially weighing 250 to 300 g were divided into control group (C, n=9), untreated; exposed group (E, n=12) were subjected to the protocol of smoke exposure cigarette (SEC) at a rate of 40 cigarettes/day; trained control group (CT, n=12), submitted to the protocol of physical training (PT ) with swimming for an hour each day, five days a week ; trained group exposed (TE, n=12) underwent protocol SEC and PT; during the study period 12 weeks. The hemodynamic records were performed by catheterization of the left ventricle. The animals were weighed weekly to monitor the growth curve. The morphometric analysis was performed by direct weighing of the left and right ventricles and lung. As a result, we observed differences in weight gain between the animals in groups C and E in weeks 4,5 and 10, was also observed at week 10 weight difference between these two groups . The morphometry factor exposure significantly increased the weights of LV/BW (2.23±0.04) and RV+LV/BW (2.79±0.05). The factor weight training significantly increased the RV/BW and lung/BW (0.58±0.01, 4.96±0,0,12) respectively. To analyze the hemodynamic factor training had significantly lower for PS Max, Pressure Developed and MAP (135.3 ± 3.3, 131.1 ± 3.3, 117.9±4.8). The E group had higher + dp/dt (3832.8±395.3), being different from groups C and TE (3294.8± 429.2, 3098.5±484.2), respectively, of -dp/dt (-3128.7±379.4), being different from groups C and TE (-2610.1±310.0, -2477.0±538.1), respectively. In conclusion, the results demonstrated that exposure to cigarette smoke promotes cardiac remodeling with increased values morphometric heart. The remodeling process was accompanied by increased left intraventricular pressure and change in velocity of contraction and relaxation of the LV. Already training with swimming exercises protection over the elevation of left intraventricular pressure, speed of contraction and relaxation of the LV. However, training associated with exposure to cigarette smoke potentiates left ventricular hypertrophy